Classical chaos and harmonic generation in laser driven nanorings. (22nd November 2016) - Castiglia, Giuseppe; Corso, Pietro Paolo; Cricchio, Dario; Giovannini, Umberto De; Frusteri, Biagio; Fiordilino, Emilio
Abstract: A quantum ring driven by an intense laser field emits light in the form of high-harmonic radiation resulting from the strong acceleration experienced by the active electrons forced to move on a curved trajectory. The spectrum of the emitted light is rich and strongly dependent on the parameters of the problem. In order to investigate the physical origin of such variability, we focus on the seemingly simple problem of a laser-driven charge constrained to a ring from a classical standpoint. As it turns out, the dynamics of such a classical electron is governed by a nonlinear equation which results into a chaotic motion—by nature depending on the initial conditions in an unpredictable way. Our results indicate that the quantum harmonic spectra are reminiscent of the classical counterpart and suggest the existence of a line connecting the quantum and classical realms.